TECHNOLOGICAL DISRUPTION IN P&C INSURANCE: THE IMPACT OF ADVANCED ANALYTICS ON RISK ASSESSMENT AND CUSTOMER ENGAGEMENT - Rajesh Kumar Srirangam; Sudheer Chennuri; Vasudev Pendyala (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
This article examines the transformative role of technological advancements in reshaping analytical practices within the property and casualty (P&C) insurance industry. By leveraging innovations such as big data analytics, artificial intelligence, machine learning, and the Internet of Things, insurers are revolutionizing their approach to risk assessment, underwriting, and claims management. The article explores how these technologies enable more accurate pricing models, personalized products, and enhanced fraud detection capabilities. Furthermore, it investigates the impact of advanced analytics on customer experience, discussing how data-driven insights foster improved engagement and loyalty. The article also addresses emerging trends, including telematics and blockchain technology, while considering the challenges insurers face in adopting these innovations, such as data privacy concerns and regulatory compliance. Through a comprehensive analysis of current practices and future possibilities, this article provides valuable insights into the ongoing digital transformation of the P&C insurance sector, highlighting the critical importance of embracing technological advancements to maintain competitiveness in an increasingly dynamic marketplace.